Technology News - No. 537 - NIOSH Develops New Mine Refuge Chamber Training (The National Institute for Occupational Safety and Health (NIOSH), 2009)
The objective is to provide effective training on refuge chambers for underground coal miners. This training will increase knowledge about how to teach miners to operate, transport, and inspect a refuge chamber; what to expect psychologically and physiologically inside a refuge chamber; and how to decide when to use a refuge chamber. Background During 2006?2007, several disasters occurred at U.S. underground coal mines, resulting in 28 fatalities. These disasters led to new approaches to mine safety and health, as well as new federal regulations. One new technology mandated by federal legislation is the refuge chamber. Refuge chambers are movable shelters that are either made of steel or inflate from a steel skid as a tent. They can potentially save the lives of miners during an underground mine emergency by providing breathable air, food, water, and a safe environment for up to 96 hours. Because the refuge chamber is a new technology, recommendations, information, and training products are greatly needed.